1993
DOI: 10.1099/00222615-39-6-416
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three molecular typing methods in studies of transmission of Porphyromonas gingivalis

Abstract: Summary. Porphyromonas gingivalis is associated strongly with severe periodontitis, but little information is available on possible transmission routes of this species. This study evaluated three DNA-based molecular typing methods for use in epidemiological surveys of P. gingivalis. In total, 32 isolates from eight married couples were investigated by : (i) restriction endonuclease analysis (REA) of whole chromosomal DNA; (ii) hybridisation of DNA fragments with ribosomal DNA (ribotyping); and (iii) amplificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 16 publications
2
27
0
1
Order By: Relevance
“…As the RAPD profiles have only a small number of bands and, consequently, are much easier to read than the corresponding REA patterns, they should be considered helpful for epidemiological and transmission studies of mutans and other oral streptococci, as already shown with P. gingivalis [27] and suggested for mutans streptococci [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the RAPD profiles have only a small number of bands and, consequently, are much easier to read than the corresponding REA patterns, they should be considered helpful for epidemiological and transmission studies of mutans and other oral streptococci, as already shown with P. gingivalis [27] and suggested for mutans streptococci [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…They include DNA-DNA hybridisation [1,12,14], restriction endonuclease analysis (REA) [16][17][18][19], multilocus enzyme electrophoresis (MLEE) [20], ribotyping, PCR and colony hybridisation with DNA probes [21]. A PCR-based procedure of DNA fingerprinting, called arbitrarily primed PCR (AP-PCR) [22] or randomly amplified polymorphic DNA (RAPD) analysis [23], has been applied to strain identification and typing of oral bacteria [24][25][26][27], oral streptococci [28][29][30] and non-oral streptococci [31][32][33][34]. The present study used RAPD analysis for typing S. mutans and S. sobrinus strains and to explore the potential of this typing method to distinguish these from the other taxa that comprise the group of mutans streptococci.…”
Section: Introductionmentioning
confidence: 99%
“…These methods include restriction endonuclease analysis (10,27,31), restriction fragment length polymorphism (RFLP) (8), ribotyping (27,31), AP-PCR (1, 27, 31), multilocus enzyme electrophoresis (19), heteroduplex analysis (26), and fimA genotyping (23). The genotypic characterization of the P. gingivalis strains has revealed extensive heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…In P. gingivalis, interspousal transmission was detected in 20 to 75% of cases by AP-PCR or a heteroduplex analysis of the ribosomal ISR. However, transmission from parent to child appeared to be uncommon (2,31). Nevertheless, the finding that concordance in the colonization of P. gingivalis was frequently observed for children and their mothers by detecting the presence of P. gingivalis by PCR assay may implicate the vertical transmission of this bacterium (30,33).…”
Section: Vol 42 2004mentioning
confidence: 99%
“…P. endodontalis와 P. gingivalis는 근관감염의 급성증상과 밀접한 관련이 있었고, P. intermedia와 P. nigrescens는 증상과 관계없 이 관찰되었다 22,23) . 24,27,28) . 또한 PCR은 세균 의 대한 DNA sequence 자료가 부족하여 모든 세균에 대 해 적용할 수 없는 단점을 가지며 특정한 균에 대해서만 특 이적인 primer를 제작하여 동정하고자 하는 세균의 DNA 와 모든 의심되는 균의 primer를 반응시켜 증폭시키는 과 정이 필요하다.…”
unclassified